Case report: The activity of multi-kinase VEGF inhibitor, Pazopanib, in metastatic undifferentiated round cell sarcomas harboring EWSR1::CREM fusion: clinicopathological series of two cases and literature review - Campoverde, Leticia; Camacho, Felipe; Alessandrino, Francesco; Evans, Mark G.; Elliot, Andrew; Rosenberg, Andrew; Trent, Jonathan (Frontiers in Oncology, 2023)
Soft tissue sarcomas harboring EWSR1::CREM fusion are rare and challenging to treat. Pazopanib, a multi-tyrosine kinase inhibitor, is FDA-approved for advanced soft tissue sarcomas, but predictive biomarkers for its efficacy remain unidentified. We conducted a study on > 240,000 neoplasms submitted to Caris Life Sciences (Phoenix, AZ) to detect rearrangements using whole transcriptome sequencing. Two sarcoma-experienced, board-certified pathologists performed histological reviews, and treatment/outcome information was collected. Among the identified cases (n = 18), we observed a diverse range of sarcoma and other cancers, including an intracranial myxoid mesenchymal tumor, mesothelioma, hyalinizing clear cell carcinomas of the head and neck, clear cell sarcomas, and undifferentiated round cell sarcomas, as well as histologically malignant tumors with epithelioid morphology. Notably, two undifferentiated, metastatic, abdominal round cell sarcoma cases treated with pazopanib demonstrated significant sustained partial response and clinical benefit. To explore the genetic factors associated with the efficacy of pazopanib in these cases, next-generation sequencing and fluorescence in situ hybridization were analyzed for alterations in the tumors. The genomic analysis provided compelling evidence confirming the presence of EWSR1::CREM fusion in both cases, with no other pathogenic gene variants or copy number alterations detected. These cases demonstrate the potential of Pazopanib as a promising therapeutic option for patients with EWSR1::CREM fusion-positive soft tissue sarcomas, including metastatic undifferentiated round cell sarcomas. The sustained clinical benefit and partial responses observed in these cases warrant further research to validate these findings and explore the wider utility of Pazopanib in this rare and challenging subset of soft tissue sarcomas. Case studies: Case 1: A 49-year-old man presented with abdominal pain, weight loss, and chronic cough. A computed tomography (CT) of the chest, abdomen, and pelvis showed multiple lung nodules and masses and a right rectus mass that was biopsied and revealed an undifferentiated round cell sarcoma with a rare fusion EWSR1-CREM. No additional pathogenic gene variants or copy number alterations were detected. He received neoadjuvant chemotherapy with three cycles of Vincristine, Adriamycin, and Ifosfamide (VAI) and seven cycles of Vincristine/Irinotecan and Temodar (VIT). After cycle 7 of VIT, he had surgical resection of the abdominal mass and received radiation for lung metastasis. He completed 13 cycles of VIT after which he presented with progression of disease and switched to monotherapy with Pazopanib. At the time of this analysis he had stable disease for 28 months. Case 2: A 75-year-old woman presented with pelvic pain and new onset constipation. CT abdomen showed a large pelvic mass and intraperitoneal tumor spread. Exploratory laparotomy revealed a ruptured pelvic mass and a small bowel tumor. Both tumors were proved to be high-grade, poorly differentiated sarcoma. Genomic analysis demonstrated an EWSR1::CREM fusion but no other pathogenic gene variants or copy number alterations. She was treated initially for a primitive neuroectodermal tumor (PNET) with four cycles of Vincristine/Adriamycin/Cytoxan/Olaratumab but declined additional chemotherapy after progression. Two years later, she presented with recurrent abdominal mass and received one cycle of Temodar/Irinotecan, then she began Pozapanib and underwent palliative radiation to the entire pelvis. She has been on Pazopanib for 23 months with stable disease.